Listeria monocytogenes MDR transporters are involved in LTA synthesis and triggering of innate immunity during infection - Tadmor, Keren; Pozniak, Yair; Burg Golani, Tamar; Lobel, Lior; Brenner, Moran; Sigal, Nadejda; Herskovits, Anat A. (Frontiers in Cellular and Infection Microbiology, 2014)
Multi-drug resistance (MDR) transporters are known eponymously for their ability to confer resistance to various antimicrobial drugs. However, it is likely that this is not their primary function and that MDR transporters evolved originally to play additional roles in bacterial physiology. In Listeria monocytogenes a set of MDR transporters was identified to mediate activation of innate immune responses during mammalian cell infection. This phenotype was shown to be dependent on c-di-AMP secretion, but the physiological processes underlying this phenomenon were not completely resolved. Here we describe a genetic approach taken to screen for L. monocytogenes genes or physiological pathways involved in MDR transporter-dependent triggering of the type I interferon response. We found that disruption of L. monocytogenes lipoteichoic acid (LTA) synthesis results in enhanced triggering of type I interferon responses in infected macrophage cells yet does not impact bacterial intracellular growth. This innate immune response required the MDR transporters and could be recapitulated by exposing macrophage cells to culture supernatants derived from LTA mutant bacteria. Notably, we found that the MDR transporters themselves are required for full production of LTA, an observation that links MDR transporters to LTA synthesis for the first time. In light of our findings, we propose that the MDR transporters play a role in regulating LTA synthesis, possibly via c-di-AMP efflux, a physiological function in cell wall maintenance that triggers the host innate immune system.